ADSORPTION KINETICS OF METHYL ORANGE ON SILICA DERIVED FROM GAMALAMA VOLCANIC SOIL - Cipta, Indra; Baturante, Nur Jannah; Hernawan, Hernawan; Rombe, Yunita Pare; Mahmudha, Siti (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
Silica gel was successfully synthesized from Gamalama volcanic soil using the sol-gel method and applied as an adsorbent to remove methyl orange (MO) dye. The synthesis process involved treating 20 grams of volcanic soil with 2 M HCl under stirring for 3 hours, followed by a 12-hour soaking period. The solid residue was subsequently filtered, dried, and reacted with 7 M NaOH for 2 hours. The resulting filtrate was neutralized through repeated washing with distilled water, and silica gel formation was achieved by titration with 2 M HCl until a final pH of approximately 3–4 was reached. The synthesized silica was evaluated for its adsorption performance against methyl orange, with optimal conditions identified at pH 4, a contact time of 5 hours, and an adsorbent dosage of 30 mg. UV-Vis analysis showed that the synthesized silica exhibited a higher adsorption capacity (6.7%) compared to raw Gamalama volcanic soil. Kinetic studies indicated that the adsorption process followed a pseudo-second-order model, suggesting chemisorption as the dominant mechanism. The rate constant (k₂) for the synthesized silica was 0.09 M⁻¹·h⁻¹, compared to 0.077 M⁻¹·h⁻¹ for the raw volcanic soil. This indicates that the synthesized silica adsorbed MO more rapidly, likely due to its higher purity and greater availability of active sites. The slightly lower k₂ observed in raw volcanic soil might be attributed to the presence of clay minerals such as halloysite and allophane, which possess negative surface charges at neutral to alkaline pH levels, leading to electrostatic repulsion with the negatively charged MO anions. Silica gel synthesized from Gamalama volcanic soil demonstrates promising potential as an eco-friendly adsorbent for dye removal from aqueous solutions.